Generation of high-power subnanosecond electron beams in diode with explosive emission; Proceedings of VIIth International Symposia on Discharge and Electrical Insulation in Vacuum, Novosibirsk, 1976 - Kovalchuk B. M. (1976, 1976)
В фонде НТБ ТПУ отсутствует